KINERJA ORGANISASI SISTEM ADMINISTRASI MANUNGGAL SATU ATAP DALAM PENERBITAN SURAT TANDA NOMOR KENDARAAN DI KANTOR SAMSAT KOTA PALU - Indraningsih, G.A. Kristha Adelia (Katalogis, 2016)
The purpose of this study was to find out the organisation performance of One Roof Administrative System (Sistem Administrasi Manunggal Satu Atap â€“ SAMSAT) in publishing vehicle registration numbers at the SAMSAT Office of Palu City. The types of data used were primary and secondary data. The data collection techniques in this study were observations, interviews, and documentations. The informants of this study were determined using purposive sampling technique. The informants of this study amounted to five (5) people. Analysis of data used was the model of Miles and Huberman, namely data reduction, data presentation, and conclusion. The theory used was the theory of Agus Dwiyanto. The organisation performance of One Roof Administrative System had been good in terms of the productivity indicator that had already been disciplined and completing tasks on time, the quality of service indicator that was assessed from the transparency that had already been done by making information board, the accountability indicator that had been carried out each month by making a monthly reconciliation, and there were good responsiveness and not good responsibility from the employees, but it was sorely lacking in infrastructure.Â